A Novel Sarsolenane Diterpene as a PTP1B Inhibitor from Hainan Soft Coral Sarcophyton trocheliophorum Marenzeller. Issue 8 (7th June 2017) - Liang, Linfu; Wang, Jinan; Shi, Xiaoxuan; Zhu, Yinghua; Li, Jia; Zhu, Weiliang; Wang, Heyao; Guo, Yuewei
Abstract : A novel sarsolenane diterpene, named secodihydrosarsolenone (1 ), as a minor component was obtained from the South China Sea soft coral Sarcophyton trocheliophorum Marenzeller. Its structure was elucidated by detailed spectroscopic analysis. Compound1 exhibited moderate inhibitory activity (IC50 =13.7 µmolL −1 ) against protein tyrosine phosphatase 1B (PTP1B), a key target for the treatment of type 2 diabetes, representing the first report of PTP1B inhibitory activity for sarsolenane diterpenes. This discovery promotes computational prediction of binding mode between the enzyme and the metabolite, suggesting a crucial role of the residues Tyr46, Ser216 and Arg221 in the binding action. Abstract : A novel sarsolenane diterpene1 as a minor component from the South China Sea soft coral S. trocheliophorum, exhibited moderate inhibitory activity (IC50 = 13.7 µmolL −1 ) against PTP1B. This discovery promotes computational prediction of binding mode between the enzyme and the metabolite, suggesting a crucial role of the residues Tyr46, Ser216 and Arg221 in the binding action.